The Regulatory Framework Regarding The Offences Against Coral Reefs In Achieving Sustainable Development Goal 14 - Izza Elvany, Ayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The purpose of this research is to analyze the regulatory framework regarding the offences against coral reefs to ensure stringent law enforcement. The research methods that are used in this study are the statute approach and conceptual approach. The analysis of the research showed that the regulatory framework regarding the offences against coral reefs is Law No.1 of 2014 amending Law No. 27 of 2007 concerning the Management of Coastal Area and Isles, especially Article 73 paragraph (1) letter a. The article recognized both an individual and a corporation as a legal person yet there is no article regarding corporate criminal liability. Furthermore, the article has the element of intentionally meaning the article adopted the principle of geen straf zonder schuld. Additionally, the analysis showed that the offences against coral reefs regardless of the used method is hindering the sustainable development goals (SDGs) achievement. Regarding the criminal punishments, to achieve the balance of coral reefs sustainability and public welfare, this research recommends the article to regulate the payment of compensation as a penal measure.